2017
DOI: 10.3390/molecules22061012
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Characteristics and Volatile Components of Dry Dog Foods Manufactured with Sorghum Fractions

Abstract: Descriptive sensory analysis and gas chromatography-mass spectrometry (GC-MS) with a modified headspace solid-phase microextraction (SPME) method was performed on three extruded dry dog food diets manufactured with different fractions of red sorghum and a control diet containing corn, brewer’s rice, and wheat as a grain source in order to determine the effect of sorghum fractions on dry dog food sensory properties. The aroma compounds and flavor profiles of samples were similar with small differences, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…In this study, they were indeed related to the mushroom-like attribute in MRPs. Hexanal (DE4) reported to have association with green, fruity [ 19 ] and fat or tallow odors [ 34 ] was actually related to the mushroom-like attribute in this study. On the other hand, MRP100 and MRP110 occurred in the left-hand lower quadrant while MRP115 and MRP120 grouped in the middle; they are significantly distinguishable from MRP140 and MRP125 which located on the right and upper side of the plot, respectively.…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…In this study, they were indeed related to the mushroom-like attribute in MRPs. Hexanal (DE4) reported to have association with green, fruity [ 19 ] and fat or tallow odors [ 34 ] was actually related to the mushroom-like attribute in this study. On the other hand, MRP100 and MRP110 occurred in the left-hand lower quadrant while MRP115 and MRP120 grouped in the middle; they are significantly distinguishable from MRP140 and MRP125 which located on the right and upper side of the plot, respectively.…”
Section: Resultsmentioning
confidence: 56%
“…There was an average of 175.40 ng/g for MRPs while the content of aldehyde for MH was only 39.94 ng/g. It was widely reported that aldehydes often possess low thresholds, in the range of a few micrograms per liter water, and thus can play a major role in odor contribution, even if present in low concentrations [ 34 ]. Hexanal, which is described to possess a grass-like and leaf-like aroma [ 19 ], showed a concentration range varying from 25.56 ng/g in MRP140 to 41.33 ng/g in MRP100.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each panelist had a broad background of experience in odor description and evaluation. Profiles from this and similar panels have been used extensively in sensory testing of chemicals and food and other products (e.g., [ 16 , 17 , 18 , 27 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]).…”
Section: Methodsmentioning
confidence: 99%
“…Certain fermentable fibers, defined as prebiotic fibers, promote the development of a beneficial gut microflora, which can help reduce the colonization of harmful bacteria [29]. Depending on the plant raw material used for production, the composition of the fiber fraction, as well as concentration of volatile compounds [30] in the final product is different. Comparing cereal and cereal-free foods for dogs, Pezzali and Aldrich [31] concluded that dietary fiber digestibility was 31.9% greater for dogs fed a diet that did not include cereals.…”
Section: Basic Compositionmentioning
confidence: 99%